2021
DOI: 10.51710/jias.v38i1.128
|View full text |Cite
|
Sign up to set email alerts
|

Facies Architecture and Sedimentary Structures in the drill cores of Uranium Bearing Sediments of Banganapalle Formation of Palnad Sub-basin, Guntur District, Andhra Pradesh

Abstract: The Banganapalle Formation, the lowest member of the Neoproterozoic Kurnool Group of rocks, resting over the basement granites, has been identified as the host rock for uranium in Koppunuru area in the western part of Palnad sub-basin. The uppermost arenite facies of the Banganapalle Formation is exposed on surface and shows only few bedform indicators like ripple marks, planer laminations etc. Down-hole lithological examinations on course of core drilling in Koppunuru and adjoining areas identified five recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…According to Deconinck et al (2005) and Dera et al, (2009), clay minerals study is considered to be a powerful tool for the interpretation of weathering conditions and paleoclimate in the source area while Da-Peng et al (2012) documented that trace and rare earth element geochemical study of ne-grained sediments, in most cases are assumed to give a clue to the average composition for the upper continental crust (UCC) more than any other sedimentary rock, because, they preserve the signature of the precursors and diagenetic history (Mondal et al, 2012;Madhavaraju et.al., 2016). Some authors, although not limited to Cullers, 2000Cullers, , 2002Gupta et al, 2012;Raza et al, 2012; Armstrong-Altrin, 2009; Fatima and Khan, 2012; Madhavaraju, 2015; Ramachandran et al, 2016 have demonstrated that geochemical compositions of clastic sediments are helpful in understanding the source-area weathering conditions and provenance. Although, chemical weathering, modi cation in redox conditions and post-depositional diagenesis can rework the main chemical composition of the shale (Nesbitt et al, 1996;Armstrong-Altrin et al, 2015;Madhavaraju, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to Deconinck et al (2005) and Dera et al, (2009), clay minerals study is considered to be a powerful tool for the interpretation of weathering conditions and paleoclimate in the source area while Da-Peng et al (2012) documented that trace and rare earth element geochemical study of ne-grained sediments, in most cases are assumed to give a clue to the average composition for the upper continental crust (UCC) more than any other sedimentary rock, because, they preserve the signature of the precursors and diagenetic history (Mondal et al, 2012;Madhavaraju et.al., 2016). Some authors, although not limited to Cullers, 2000Cullers, , 2002Gupta et al, 2012;Raza et al, 2012; Armstrong-Altrin, 2009; Fatima and Khan, 2012; Madhavaraju, 2015; Ramachandran et al, 2016 have demonstrated that geochemical compositions of clastic sediments are helpful in understanding the source-area weathering conditions and provenance. Although, chemical weathering, modi cation in redox conditions and post-depositional diagenesis can rework the main chemical composition of the shale (Nesbitt et al, 1996;Armstrong-Altrin et al, 2015;Madhavaraju, 2015).…”
Section: Introductionmentioning
confidence: 99%